2021
DOI: 10.1016/j.jcbs.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting personal protective equipment use, trauma symptoms, and physical symptoms in the USA during the early weeks of the COVID-19 lockdown (April 9–18, 2020)

Abstract: The COVID-19 pandemic created a complex psychological environment for Americans.In this study, 450 MTurk workers completed measures of sociodemographic characteristics, perceived risk for COVID-19, general perceived vulnerability to disease, intolerance of uncertainty, and psychological flexibility. These variables were used to predict COVID-19 preventive health behaviors (PPE use), psychological distress, and physical symptoms. The surveys were completed between April 9, 2020 and April 18, 2020 which is a per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The responses were ranging from “Strongly disagree” (1) to “Strongly agree” (5) for each item (e.g., "My past experiences make me believe I am not likely to get sick even when my friends are sick." Our prior examination of the psychometric properties of the PVD revealed suboptimal Cronbach's alphas [4] . An exploratory factor analysis with an oblimin rotation was conducted to determine subscales that match the present sample.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…The responses were ranging from “Strongly disagree” (1) to “Strongly agree” (5) for each item (e.g., "My past experiences make me believe I am not likely to get sick even when my friends are sick." Our prior examination of the psychometric properties of the PVD revealed suboptimal Cronbach's alphas [4] . An exploratory factor analysis with an oblimin rotation was conducted to determine subscales that match the present sample.…”
Section: Methodsmentioning
confidence: 92%
“…The demographic items employed for gender, ethnicity, and religion are from the USA census items [3] . These were later combined with items previously used in mindfulness and health investigations [4] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in the United States researchers found that individuals with greater psychological flexibility experienced reduced psychological distress during the COVID-19 pandemic [10]. Other studies have further investigated psychological flexibility as it relates to the pandemic in different outcomes, as well as the potentially protective effects of psychological flexibility on mental health during the pandemic [26][27][28][29]. As such, it is clear that psychological flexibility is an important modifiable transdiagnostic predictor of well-being and behavioral compliance during global adversity.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggested that when conversations among individuals focus on increasing perspective and understanding rather than dwelling on negative experiences, they ameliorate emotional distress and promote committed action. Similarly, O'Brien and colleagues (2020) presented analyses in a sample of 450 Mturk workers in the US taken in April 2020. Although their analyses suggested that psychological inflexibility and intolerance of uncertainty were both linked to psychological distress and physical symptoms, moderation analyses suggested that psychological flexibility buffered the links between intolerance of uncertainty and those outcomes, highlighting psychological flexibility as a source of resiliency.…”
mentioning
confidence: 99%